Familiar quotations : a collection of passages, phrases, and proverbs traced to their sources in ancient and modern literature - Bartlett, John, 1820-1905 (Boston : Little Brown, 1952)
Chronologically arranged entries supply quotations from 2,250 authors and major collective or anonymous works, with an alphabetical index of authors and an index to the text.
Includes indexes.
Includes indexes.
Keywords: Quotations, English; Quotations